ANTIOXIDANT THERAPY STIMULATES RECOVERY OF INJURED NERVE IN TERMS OF MERCURY INTOXICATION - Shamalo, S.N. (World of Medicine and Biology, 2015)
One of the major problems of modern medicine are restoration of the peripheral innervation due to injury. Treatment does not always lead to the desired results. Most experimental work on the issue of the regeneration of peripheral nerves do not take into account the state of the environment. One of the leading exogenous environmental pollutants takes mercury and its salts. Even in small concentrations in the long-term effects they can cause neuropathy, which will complicate the process of regeneration of injured nerve. Therefore, it remains the search for new pharmacological agents that stimulate recovery processes under conditions of intoxication. The aim of this study is to examine the impact Thiotriazoline recovery of peripheral nerve in terms of mercury intoxication. In experiments on white rats, which were divided into 4 groups, recreated the standard model of sciatic nerve injury in conditions of chronic subhronical micromercurialism. Postoperatively, the rats of the first and third groups pharmacotherapy not performed, and the second and fourth groups of animals were injected intraperitoneally daily for 2 weeks, Thiotriazoline solution at a dose of 100 mg / kg. We studied the morphological organization and morphometric characteristics of regenerative neuroma and adjacent segments (proximal and distal) sciatic nerve in 12 weeks after injury. The study found that in the central segment of the sciatic nerve rats under chronic intoxication and subhronichnoyi are rising irritation and degeneration that gradually decrease. But even at 12 weeks after injury kept weak edema and irritation of nerve fibers in the form of waviness and uneven contours of their location. connective tissue becomes weak signs of differentiation. This is evidenced by the increase bundles of collagen fibers and reduce the number of cellular elements of connective tissue and rarer zones with reduced vascular ensuring. In peripheral segment of sciatic nerve degeneration observed descending. Regenerating nerve fibers sprouting in small amounts through a neuroma distal segment and retain irritation in the form of waviness contours. Application Thiotriazoline significantly reduces the average deviation angle from the longitudinal axis of the axon nerve neuroma in the area at different times of observation, quantitative and increases density of nerve fibers distal second and fourth groups. Morphometric data suggest that groups of animals who underwent pharmacological correction Thiotriazolin activated nerve regeneration in the conditions of mercury intoxication.